Pemetaan Kejadian Stunting di Wilayah Kerja Puskesmas Bati Berdasarkan Ketersediaan Air Bersih - Skhana Marthinus Sanam; Imelda Manurung; Sigit Purnawan (Media Kesehatan Masyarakat, 2021)
This study aims to map the spread of stunting cases based on the availability of clean water. This study used descriptive method to see the frequency of disease by place using Geographic Information System (GIS). The population in this study was children under five years diagnosed with stunting. All population was sampled (total sampling) with a total of 119 cases. The results showed that stunting spread throughout the work area of Bati Primary Health Care (PHC) with the availability of 67 water sources. Most widely used sources were wells (46 in total) and located in areas with an altitude of >1000 meters above sea level. Intensive government stunting efforts are necessary as stunting is a nutritional health issue prioritized in the National Medium-Term Development Plan period 2019-2024. Improving the education of Clean and Healthy Living Behavior (PHBS) for the community and strengthening commitment and cooperation with relevant parties are required to address the problem of adequate nutrition intake, and water supply in the community.